Multiple-input single-output antenna schemes for DVB-NGH - Robert, Jörg; Zöllner, Jan (CRC Press, 2013)
MISO stands for multiple-input, single-output and describes a radio link that uses at least two transmitters but only one receiver. A conventional topology comprising a single transmitter and a single receiver is referred to as single-input, single-output (SISO). This chapter gives an overview of MISO technology as employed within Digital Video Broadcasting-Next Generation Handheld (DVB-NGH). This comprises firstly the Alamouti scheme that is already well-known from DVB-T2 (terrestrial second generation) and the enhanced single-frequency network (eSFN) scheme.
CRIS-Team Scopus Importer:2024-11-19